ANALYSIS OF AIR POLLUTION DISPERSION IN BANDUNG CITY USING WRFCHEM DATA ASSIMILATION - Pratama, Alvin
Air pollution is one of the main problems in the big cities in Indonesia, one of them is Bandung City. This problem arises due to the increasing need and level of activities carried out by humans, such as industrial activities, the use of vehicles, and land clearing. This is one of the triggers for the increasing concentration of pollutants in the atmosphere that can affect the lives and welfare of humans or ecosystems. Basically, the level of concentration and movement of pollutants in the atmosphere is influenced by various factors, such as meteorological conditions (wind direction and speed, rainfall, temperature, pressure), topographic characteristics, and sources of emissions. To determine the movement and concentration level of these pollutants, a simulation was carried out using the WRFCHEM model. This simulation utilizes AWS (Automatic Weather Station) data and Bandung city emissions inventory data using the assimilation method. Data assimilation aims to improve the initial condition and boundary condition of the model and verify the results of the model. From the simulation results, it was found that the main emissions of the Bandung city were predominantly sourced from motor vehicles which were dominated in the south, namely the Padaleunyi toll road and Jalan Soekarno Hatta. While the use of assimilation data in the WRFDA model, it can increase meteorological parameter accuracy up to 1-7%. On the other hand, the distribution of pollutants in the Bandung city is strongly influenced by local and monsoon factors. In the dry month, pollutants tend to spread to the northward and westward, while in the wet months tend to spread to the southward and eastward. In addition, the high wind speed in the dry months (from the southward and southeastward) and the flat topographic character (in the south) causes PM10 to spread out of the Bandung city. While in the wet month, the weakening of the wind speed due to the complex topography in the north of Bandung city causes PM10 to not be well dispersed. On the other hand, the effect of wet deposition in end of March did not significantly affect the level of concentration reduction in the wet month. From the results of the simulation, there are also some areas that need to be prioritized in air quality management when compared with the quality standards based on PP 41 of 1999. Areas that need special attention include Rancabolang, Mekarjaya and Pasirluyu.